2023
DOI: 10.1002/imt2.122
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and drivers of microbiome in different rock surface soil under the volcanic extreme environment

Abstract: Soil microbial communities were investigated under the volcanic extreme environment. Soil bacterial networks exhibited higher stability than fungal networks. Holocene granite had a more complex microbial network than basalt. Soil pH and total protein were key drivers of microbial network stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Additionally, nitrate reductase ( NarG ) was in class 0 and can be represented by landmark genes that encode superoxide dismutase ( SOD ) and 4‐hydroxy‐tetrahydrodipicolinate synthase ( DapA ), both of which were critical enzymes in antioxidant systems, mainly involved in superoxide scavenging. This was also supported by the domain role of SOD in determining the microbial network in a previous study [ 35 ].…”
Section: Resultssupporting
confidence: 79%
“…Additionally, nitrate reductase ( NarG ) was in class 0 and can be represented by landmark genes that encode superoxide dismutase ( SOD ) and 4‐hydroxy‐tetrahydrodipicolinate synthase ( DapA ), both of which were critical enzymes in antioxidant systems, mainly involved in superoxide scavenging. This was also supported by the domain role of SOD in determining the microbial network in a previous study [ 35 ].…”
Section: Resultssupporting
confidence: 79%
“…3 ). The network was constructed using the top 100 fungal ASVs of key soil microbial communities [ 27 ]. The CK network consists of 245 nodes and 6,681 edges.…”
Section: Resultsmentioning
confidence: 99%
“…In agricultural soils, the myriad of microbes lives together and form complex interconnected microbial networks, where microbes associate with each other directly or indirectly through processes, such as competition, predation, and mutualism ( de Vries et al, 2018 ; Wagg et al, 2019 ). It is theoretically expected that microbial communities with more complex associations will have more active metabolic processes and faster growth rates, resulting in improved community performance ( Brown et al, 2004 ; Chen et al, 2023 ; Jordan, 2009 ). Previous researchers have tried to link microbial network complexity to ecosystem multifunctionality ( Chen et al, 2022 ; Wagg et al, 2019 ), and Chen et al (2022) reported that soil microbial network complexity contributed more to multifunctionality than diversity.…”
Section: Introductionmentioning
confidence: 99%